Investigation of the regenerative potential of necrotic mature teeth following different revascularisation protocols - Hossam Fahmy, Sarah; Hassanien, Ehab El Sayed; Nagy, Mohamed Mokhtar; Batouty, Kariem Mostafa El; Mekhemar, Mohamed; Sayed, Karim Fawzy El; Hassanein, ElHassan; Wiltfang, Jörg; Dörfer, Christof (Australian endodontic journal, 2017)
This study aimed to assess the revascularisation potential of necrotic mature teeth in a dog model following different protocols. Periapical infection was induced in 54 mature premolars. Teeth were distributed into seven groups: (1) Double-antibiotic-paste/Blood clot, (2) Ciprofloxacin/collagen, (3) Double-antibiotic-paste/Collagen, (4) Modified Tri-antibiotic-paste /collagen, (5) Ciprofloxacin/Gelfoam, (6) Double-antibiotic-paste/Gelfoam, and (7) Modified Triantibiotic- paste/Gelfoam. Positive and negative controls included infected and healthy teeth, respectively, (n = 12 roots/group). Canals were apically shaped to size 0.6 mm then disinfected for 1 month. Intra-canal bleeding was induced then scaffolds were applied for another month. Teeth and supporting bone were surgically sampled. Tissues were histologically scored and vimentin immuno-intensity was estimated. Ciprofloxacin and Double-antibiotic paste/Collagen resulted in significantly better corono-apical tissue ingrowths, vascularity, cementum formation and significantly lower inflammatory extents (P < 0.05).These groups also showed significantly higher Vimentin intensities, (P < 0.05). The applied protocols revascularised necrotic mature canals and reduced inflammation particularly in the Ciprofloxacin/collagen and Double-antibiotic-paste/collagen groups.